Immune Response in Severe Infection: Could Life-Saving Drugs Be Potentially Harmful?. (30th September 2013) - Surbatovic, Maja; Jevdjic, Jasna; Veljovic, Milic; Popovic, Nada; Djordjevic, Dragan; Radakovic, Sonja
Abstract : Critically ill patients suffer a high rate of nosocomial infection with secondary sepsis being a common cause of death. Usage of antibiotics and catecholamines is often necessary, but it can compromise complex immune response to infection. This review explores influence of these life-saving drugs on host immune response to severe infection.